The effect of stress as a mediator in the relationship between antecedents and employee misconduct in the Royal Malaysian Police - Ismail, Mazlan; Jaharuddin, Nor Siah; Jo Ann, Ho; Mansor, Zuraina (Universiti Putra Malaysia, 2024)
Employee misconduct (EM) is a significant issue in law enforcement agencies, where officers may exploit their authority for personal gain. Grounded in the General Strain Theory (GST), General Theory of Crime (GTC) and Fraud Triangle Theory (FTT), this study aims to investigate the role of stress as a mediating factor between various antecedents (self-control, integrity, organizational justice, politics, salary, financial pressure, and lifestyle) and EM, specifically within the Royal Malaysian Police (RMP). Data was gathered through two structured questionnaires administered to both employees and their supervisors using a quantitative research design. A total of 428 police officers from Kuala Lumpur, Selangor, Johor, Perak, and Sabah participated in the study. The findings show that self-control, organizational justice, salary, and financial pressure significantly influence stress and EM, while integrity, organizational politics, and lifestyle do not. Furthermore, stress was found to partially mediate the relationship between these antecedents (self-control, organizational justice, salary, financial pressure) and EM. This study is the first to explore the mediating effect of stress on EM within a Malaysian law enforcement context, and the integration of individual, organizational, and socio-economic factors into a unified model represents a novel contribution to the study of misconduct in law enforcement agencies.